2017
DOI: 10.1038/s41598-017-11584-4
|View full text |Cite|
|
Sign up to set email alerts
|

Correlative Evaluation of Mental and Physical Workload of Laparoscopic Surgeons Based on Surface Electromyography and Eye-tracking Signals

Abstract: Surgeons’ mental and physical workloads are major focuses of operating room (OR) ergonomics, and studies on this topic have generally focused on either mental workload or physical workload, ignoring the interaction between them. Previous studies have shown that physically demanding work may affect mental performance and may be accompanied by impaired mental processing and decreased performance. In this study, 14 participants were recruited to perform laparoscopic cholecystectomy (LC) procedures in a virtual si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 48 publications
0
35
0
1
Order By: Relevance
“…Bei Stress steigt die Hf an und die HRV-Parameter weisen geringere Ausprägungen auf [2,39]. Auch die Art des durchgeführten operativen Eingriffes [7,14,18,38,44] und die Assistenz eines leitenden Chirurgen [13] hat Einfluss auf das Stressniveau und den Beanspruchungsgrad des Operateurs. So ist das Stresslevel bei chirurgischen Eingriffen ohne den Einsatz einer Herz-Lungen-Maschine ("off-pump") höher als bei solchen mit Herz-Lungen-Maschine ("onpump") [6] Objective.…”
Section: Hintergrund Und Fragestellungunclassified
“…Bei Stress steigt die Hf an und die HRV-Parameter weisen geringere Ausprägungen auf [2,39]. Auch die Art des durchgeführten operativen Eingriffes [7,14,18,38,44] und die Assistenz eines leitenden Chirurgen [13] hat Einfluss auf das Stressniveau und den Beanspruchungsgrad des Operateurs. So ist das Stresslevel bei chirurgischen Eingriffen ohne den Einsatz einer Herz-Lungen-Maschine ("off-pump") höher als bei solchen mit Herz-Lungen-Maschine ("onpump") [6] Objective.…”
Section: Hintergrund Und Fragestellungunclassified
“…Assessment of surgeon mental and physical workload can be difficult to define but are important concepts to consider as studies have shown that surgeons have musculoskeletal pain due to muscle tension and maintaining awkward poses for long periods of time in the operating room 12,13 . Additionally, mental workload can lead to job dissatisfaction and burnout 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Eye movement features can be used as an adjunct to standardize evaluation methods to overcome the difficulties described above. Eye tracking has already been used in medical fields regarding the usability of modern anesthesia ventilators evaluation [ 23 ], in the workload of laparoscopic surgeons [ 24 ], in nursing education [ 25 ], and in the ergonomic evaluation of ventilator [ 26 ]. Particularly for pupil dilatation, the technique has been shown to be sensitive to task difficulty and workload [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for pupil dilatation, the technique has been shown to be sensitive to task difficulty and workload [ 27 , 28 ]. Published studies have shown that larger pupil sizes change from baseline implies greater task difficulty and mental workload [ 24 , 26 , 29 31 ]. Therefore, the measurement of pupil diameter can be used as a standardized evaluation method for assessing the ergonomic of user-interface of ventilators.…”
Section: Introductionmentioning
confidence: 99%